2022
DOI: 10.3390/antiox11020215
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Key Components of a Standardized Centella asiatica Product in Cognitively Impaired Older Adults: A Phase 1, Double-Blind, Randomized Clinical Trial

Abstract: Centella asiatica is reputed in Eastern medicine to improve cognitive function in humans. Preclinical studies have demonstrated that aqueous extracts of C. asiatica improve cognition in mouse models of aging and Alzheimer’s disease (AD) through the modulation of mitochondrial biogenesis and nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent antioxidant response genes. This randomized, double-blind, crossover Phase I trial explored the oral bioavailability and pharmacokinetics of key compounds from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 74 publications
(129 reference statements)
3
19
1
Order By: Relevance
“…Plasma samples were prepared in duplicate for analysis by HPLC–MS/MS using methods previously described ( Cheng et al, 2003 ; Wright et al, 2022 ). Plasma samples (50 μL) and an ascorbic acid solution (1%; 10 μL) were combined with A. aerogenes sulfatase (2.5 μL; 0.025–0.05 units; Sigma-Aldrich) and E. coli glucuronidase (2.5 μL; 12.5–125 units; Sigma-Aldrich) dissolved in 50% aqueous glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma samples were prepared in duplicate for analysis by HPLC–MS/MS using methods previously described ( Cheng et al, 2003 ; Wright et al, 2022 ). Plasma samples (50 μL) and an ascorbic acid solution (1%; 10 μL) were combined with A. aerogenes sulfatase (2.5 μL; 0.025–0.05 units; Sigma-Aldrich) and E. coli glucuronidase (2.5 μL; 12.5–125 units; Sigma-Aldrich) dissolved in 50% aqueous glycerol.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, it is also reported that after oral administration of asiaticoside, it may undergo biotransformation into asiatic acid, the aglycone of asiaticoside that was also annotated as apyrase ligand in our ultrafiltration screening. Then, the hypothesis that asiatic acid may also have antischistosomal activity [ 55 ] should be further explored in the future. Thus, the precise in vivo antischistosomal mechanisms of asiaticoside must be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…DACD is described as learning and memory impairments, which are closely related to hyperglycemia. The AA with anti-oxidation, anti-inflammation and anti-apoptosis could protect against both diabetes and cognitive defect 11,12 . Previous studies showed that AA prevented organs against hyperglycemia-related injuries, such as diabetic nephropathy and diabetic cardiopathy 13 .…”
Section: Discussionmentioning
confidence: 99%